Energy efficiency monitoring system of operated irrigation pumping stations in Uzbekistan - Nazir Ikramov; Farkhod Kasimov; Mekhrbonu Rakhimova (Journal of Water and Land Development)
This study addresses the challenges of online monitoring of water metering in irrigation systems in Central Asia, specifically in the Republic of Uzbekistan. The importance of this study lies in improving water management and energy efficiency in a region where water resources are critical for agriculture. Uzbekistan, with 2.3 mln ha of irrigated land – 53% of the total agricultural area – is dependent on 1,693 pumping stations that annually pump over 50 mln m3 of water. These stations consume between 8 to 8.2 bln kWh of electricity each year, representing about 11% of the nation’s total electricity generation. Currently, energy consumption at these irrigation pumping stations is monitored manually, and most stations lack accurate water metering devices, which hinders the ability to account for sediment in the water and prevents real- time energy efficiency monitoring. Additionally, 1–3% of the electricity used by these stations is consumed by auxiliary systems, contributing to increased overall energy consumption. The primary goal of this study is to scientifically substantiate, develop, and implement a system for monitoring the energy efficiency of irrigation pumping stations in real time. This includes providing real-time data on electricity consumption and supply, as well as integrating photovoltaic systems to meet the internal energy needs of the pumping stations. The implementation of such a monitoring system is expected to optimise energy use, reduce operational costs, and enhance sustainable water management practices in Uzbekistan.